The impact of climate legislation on trade-related carbon emissions 1996-2018 - Eskander, SMSU; Fankhauser, S (Springer, 2023)
We analyse the international impact on carbon emissions from national climate legislation in 111 countries over 1996–2018. We estimate trade-related carbon leakage, or net carbon imports, as the difference between consumption and production emissions. Legislation has had a significant negative and roughly similar impact on both consumption and production emissions. The net impact on trade-related emissions is therefore not statistically significant, neither in the short term (laws passed in the last 3 years) nor the long term (laws older than 3 years). We find a significant negative long-term impact on domestic emissions from laws passed by trade partners. This latter specification corresponds to the traditional definition of carbon leakage. Overall, we conclude that there has been no detrimental effect of climate legislation on international emissions.